Las habilidades cognitivas en la resolución de problemas matemáticos - Inca Maldonado, Isabel (2019)
Approaching the teaching and learning of problem solving with a certain rigor requires awareness of the series of cognitive processes that develop in this process. It is known that many students have difficulties in learning mathematics during their schooling and in later adult life. These difficulties cause school delay, poor school performance and in the worst case, school dropout. Various investigations from different perspectives have been interested in explaining the causes of these difficulties. Among these investigations, importance is being given to Executive Functions, since they are cognitive abilities of the prefrontal cortex (PFC) that are related to each other, and include skills related to the ability to set goals, organize and plan tasks, follow sequences, initiate a plan and keep it in mind while it is being executed, inhibit distractions, change strategies flexibly if the case requires it, self-regulate and control the course of action to ensure that the proposed goal is achieved. All these functions are related to the ability to solve mathematical problems, consequently, the alteration of these, can limit the ability of the individual to maintain or carry out a mathematical activity, successfully.